2013
DOI: 10.1016/j.jpor.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional finite element analysis of the stress distribution on morse taper implants surface

Abstract: Moreover, these 5mm implants were positioned at the cortical bone level, which has higher elastic modulus and may have influenced at the stress distribution. However, despite the higher stresses, these implants were well able to withstand the applied forces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 25 publications
1
20
0
1
Order By: Relevance
“…42 Based on finite element analysis CIR was identified to play a role in stress reduction, as an increased CIR resulted in higher stress concentrations around peri-implant bone. 15 Following these findings, from a biomechanical point of view increased MBL can be expected with higher CIRs, as mechanical overloading, as well as disuse, provokes periimplant bone resorption. 26,27 As clinical CIR is considered more relevant than anatomical CIR for biomechanical analyses only clinical CIR was calculated in the present study.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…42 Based on finite element analysis CIR was identified to play a role in stress reduction, as an increased CIR resulted in higher stress concentrations around peri-implant bone. 15 Following these findings, from a biomechanical point of view increased MBL can be expected with higher CIRs, as mechanical overloading, as well as disuse, provokes periimplant bone resorption. 26,27 As clinical CIR is considered more relevant than anatomical CIR for biomechanical analyses only clinical CIR was calculated in the present study.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, it is reported that an increased CIR may not be a risk factor for dental implant failure under appropriate plaque control . Based on finite element analysis CIR was identified to play a role in stress reduction, as an increased CIR resulted in higher stress concentrations around peri‐implant bone . Following these findings, from a biomechanical point of view increased MBL can be expected with higher CIRs, as mechanical overloading, as well as disuse, provokes peri‐implant bone resorption …”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations